SURGICAL OUTCOME OF PLATE AND HOOK FIXATION FOR CRANIO-VERTEBRAL JUNCTION INSTABILITY - Sharafat, Seema; Khan, Zahid; Ahmad, Sajjad (Journal of Postgraduate Medical Institute, 2020)
Objective: To determine the surgical outcome of patients undergoing plate and laminar hooks fixation for cranio-vertebral junction (CVJ) instability. Methodology: This cross sectional study was conducted in Department of Neurosurgery, Lady Reading Hospital, Peshawar, from January 2014 to June 2017 on a sample of 13 patients enrolled with consecutive sampling. Those patients who underwent plates and laminar hook fixation for CVJ instability were included in the study irrespective of their age and gender. Clinical and radiological data of the patients were collected on preformed proforma. Pre-operative and post-operative Nurick grades at 6 months follow up were documented. Neurological improvement was taken as the main outcome variable according to change in Nurick score. The data were analyzed with SPSS version 22. Results: Total number of patients was 13 and all of them were males. The mean age was 22.80 ±17.55 years. Etiology was trauma in all the cases. The mean pre-op Nurick score was 2.46 ±1.26 and the mean post-operative Nurick score was 1.85 ±0.98, with improvement of 0.6. Post operatively one (7.60%) patient developed wound infection. Restricted neck movements were present in 12 (92.31%) patients post-operatively. Conclusion: Occipital plates and laminar hooks procedure was found effective in patients with CVJ instability in terms of neurological improvement.